Study on Hydraulic Connection and Seepage Law of Goaf Groups in Coal Mine Underground Reservoir - Wei Qin (Geofluids)
A coal mine underground reservoir, composed of a large number of goaf groups, is effective in achieving the protective utilization of coal mine water. Mastering the hydraulic connection between the goaf groups and the law of seepage is the key to the design and safe operation of coal mine underground reservoirs. Coal/rock sample seepage tests were conducted in Wanli No. 1 Mine in the Shendong mining area according to the evolution law of the lateral supporting pressure of the coal pillars. From the tests, the function of vertical stress in relation to the permeability of coal/rock samples was obtained and the distribution law of permeability of porous media in the goaf was revealed. On this basis, the computational fluid dynamics (CFD) numerical calculation of seepage properties of the coal/rock pillars was conducted. The results show that with the decrease of water level in the goaf and the increase of coal pillar width, the flow range and flow velocity keep decreasing. At the water level of 18.65, 28.65, and 38.65 m, the critical coal pillar widths for the goaf water to penetrate into the adjacent goaf are 30, 50, and 70 m, respectively. When the coal pillar width is less than 10 m, the water can bypass the elastic core area at the bottom coal seam to the adjacent goaf area; when the width exceeds 20 m, the water cannot enter the adjacent goaf area through the bottom coal pillar. On the basis of CFD simulation study on seepage properties of coal/rock pillars between goafs, this paper conducts calculations for all the goafs in the 4-2 coal-panel block of Wanli No. 1 Mine and reveals the seepage path and seepage law in the underground reservoir of this mine.